Relationship between Maternal Knowledge and Nutritional Status of Children in Teluk Patipi, Fakfak - Patiran, Kahlida; Siswati, Tri; Yuliati, Endri (Poltekkes Kemenkes Riau, 2024)
Mothers with low knowledge have 3.069 times greater potential to have underweight toddlers than mothers with good knowledge. The prevalence of undernutrition in West Papua in 2021 was 10.8% while Fakfak Regency at 6.8% and Teluk Patipi District at 12.95%. This study was aimed to now the rationship between maternal knowledge and nutritional status of children. This cross-sectional study was conducted in 62 children aged 13-60 months. Nutritional status was determined using weight for height index while maternal knowledge was assessed using a questionnaire. Mothers with poor knowledge were 69.4%. Toddlers who experienced malnutrition were 33 toddlers (53.2%). The results of the bivariate test showed that there was a significant relationship between maternal knowledge about nutrition and nutritionsl status in toddlers (P<0.05). There was a relationship between maternal occupation and the nutritional status of toddlers (p=0.023). In contrast maternal age (p=0.784), maternal education (p=0.239), child age (p=0.078), and child gender (p=0.369) did not significantly relate to the nutritional status of toddlers. There was also the relationship between maternal knowledge and the nutritional status of toddlers in Teluk Patipi Sub-district, Fakfak Regency, West Papua.